INCREASING STUDENTS’ ENTREPRENEURSHIP AWARENESS THROUGH COLLEGE TOURISM BUSINESS INCUBATORS - I Ketut Sutama; I Ketut Pasek; I Gede Mudana (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2017)
The aim of the study is to search the entrepreneurial potency of students of Politeknik Negeri Bali (State Polytechnic of Bali). By knowing such a potential, the development of tourism business incubator within the college will be significant. Instead of giving theoretical and practical benefits in terms of teaching and learning for the subject of entrepreneurship, the existence of the incubator will prove that the institution also plays the role in creating job opportunity. In terms of teaching and learning process the result of the study will give support to the subject of entrepreneurship, for instance in production of updated teaching material and method. On the other hand, regarding job creations, institutional incubator business will give wider chance to students and fresh graduates to train themselves to create and practice business. To get view on the potency of entrepreneurship of the students, a number of 91 fourth semester students were chosen as research samples. Questionnaires were distributed to them, then analyzed using descriptive method. Three indicators of entrepreneurship, such as innovation, proactive, and risk acceptance, also indicator of the potency of business in tourism area were utilized to count means. It was found the value of 3.6. It means that between 1 to 5 of choice scale, the value of 3.6 is significant enough to indicate that the students have good potency for entrepreneurship. If it is developed seriously, they will be able to build their own business upon graduate. Such a data is significant enough as an indicator for further research at the second year, dealing with the development of business incubator in tourism area.